Toward tailored exosomes: the exosomal tetraspanin web contributes to target cell selection - Rana, Sanyukta; Yue, Shijing; Stadel, Daniela; Zöller, Margot (The international journal of biochemistry & cell biology, 2012)
Exosomes are discussed as potent therapeutics due to efficient transfer of proteins, mRNA and miRNA in selective targets. However, therapeutic exosome application requires knowledge on target structures to avoid undue delivery. Previous work suggesting exosomal tetraspanin-integrin complexes to be involved in target cell binding, we aimed to control this hypothesis and to define target cell ligands. Exosomes are rich in tetraspanins that associate besides other molecules with integrins. Co-immunoprecipitation of exosome lysates from rat tumor lines that differ only with respect to Tspan8 and beta4 revealed promiscuity of tetraspanin-integrin associations, but also few preferential interactions like that of Tspan8 with alpha4 and beta4 integrin chains. These minor differences in exosomal tetraspanin-complexes strongly influence target cell selection in vitro and in vivo, efficient exosome-uptake being seen in hematopoietic cells and solid organs. Exosomes expressing the Tspan8-alpha4 complex are most readily taken up by endothelial and pancreas cells, CD54 serving as a major ligand. Selectivity of uptake was confirmed with exosomes from an alpha4 cDNA transfected Tspan8(+) lymph node stroma line. Distinct from exosomes from the parental line, the latter preferentially targeted endothelial cells and in vivo the pancreas. Importantly, pulldown experiments provided strong evidence that exosome-uptake occurs in internalization-prone membrane domains. This is the first report on the exosomal tetraspanin web contributing to target cell selection such that predictions can be made on potential targets, which will facilitate tailoring exosomes for drug delivery.